(untitled) (Ozone Therapy Global Journal, 2012)
Early evidence on the clinical use of ozonated oils first appear in scientific literature in 1859. This paper reviews the general and main clinical applications of ozonated oils that have appeared in scientific literature between 1859-2011. The oxidation products generated after the reaction of ozone with fatty acids and other substrates can acts as a germicide, immune stimulantand tissue restoration agent. The biological activities and stability of the ozonated oilsallows the development of standard formulations that deliver the benefits of ozone, supported by pre-clinical and clinical studies.The main clinical studies that support t he u se of ozonized oils apply ozonizedsun flower oil orozonizedolive oil in different clinical conditions. The applications are essentially for external use, however there is evidence of immune-stimulating and repaireffects when used orally. A deep study of the biological effects of various formulations already on the mar ket will support the scientific b asis of the use of ozoniz ed o i l in differen t pathologies.